Aquascape Media as A Tool in Learning The Interaction Between Living Creatures and The Environment to Improve Students' Mastery of Concepts and Communication Skills - Jody Febriandini; Suyanta Suyanta (Jurnal Penelitian Pendidikan IPA, 2024)
The process of learning interactions between living things and the environment requires direct observation by students, but in reality the school is located in the city center with a less than optimal surrounding environment. The availability of learning media for this material has not been widely developed by students. The research aims to produce aquascape media that is suitable as an aid in learning interactions between living things and the environment to improve students' mastery of concepts and communication skills. The research uses a 4D development model which includes Define, Design, Develop, and Dessiminate. The test subjects were taken using a cluster random sampling technique and a sample of 66 students at SMPN 12 Yogyakarta was obtained, consisting of experimental and control classes. The field test used quasi-experimental research with a nonequivalent control group design. The feasibility, teacher practicality, and effectiveness of assessing aquascape media as an aid in learning interactions between living creatures and the developed environment are included in very good and practical.